Online verbal aggression, social relationships, and self-efficacy beliefs. (May 2021) - Ferreira, Paula da Costa; Veiga Simão, Ana Margarida; Pereira, Nadia Salgado; Paulino, Paula; Oliveira, Sofia
This study aims to understand whether the relationships adolescent bystanders of cyberbullying have with the victim and other bystanders and their self-efficacy beliefs may affect their use of aggressive language online. Students (676, Mage = 14.10, SD = 2.74, 55.5% male) answered questions about social media use, self-efficacy to solve cyberbullying situations, interpersonal relationships, and their use of verbal aggression to communicate online. Through structural equation modeling, results demonstrated that having a relationship with the victim or other bystanders mediated the relationship between observing cyberbullying behavior and bystanders' use of aggressive language online. The effect of observing cyberbullying behavior through having a relationship with the victim or other bystanders was lower than its direct effect on adolescent bystanders' use of aggressive language. Self-efficacy beliefs mediated the relationship between having a relationship with the victim and other bystanders and adolescents' use of aggressive language online. Implications for intervention in interpersonal communication online are proposed.